Ethical issues of involving people with intellectual disabilities in genomic research: a scoping review protocol - Chepkirui, D; Kipkemoi, P; Bitta, M; Harris, E; Musesengwa, R; Kamuya, D (F1000Research, 2023)
Background: Psychiatric genomic research is a growing field of research in Africa that is looking at epigenetics of psychiatric disorders; within which a specific focus is neurodevelopmental disorders including intellectual disability (ID). Conducting this type of research is important to identify etiologies and possible interventions or areas for further research. However, genomic research generally, and psychiatric genomic research, faces many social, ethical, cultural, and legal issues; research involving people with ID is particularly challenging. All research stakeholders - researchers, research review bodies, regulators, patient groups - generally agree that involving people with ID require several considerations, including extra protection. It is also recognized that not involving people with ID in research that is relevant to them means that opportunities to learn on specific issues including lived experiences are missed. In this scoping review, we aim to describe the range of ethical and social-cultural issues concerning involvement of people with intellectual disability in genomic research from existing literature. Methods: This scoping review will be conducted based on the Joanna Briggs Institute guidance for scoping review and reported using the PRISMA-ScR guidelines. Iterative review stages will include systematic search of six databases (Embase, Ovid Global Health, PubMed, Scopus, PsycInfo and Web of Science core collection), screening, charting and synthesis of the data. Forward and backward citation screening will also be done for the articles included in the final review. We will include peer reviewed journal articles, guidance documents and reports. Screening and selection of studies based on the eligibility criteria will be done independently by three reviewers; conflicts will be resolved through discussion with a third reviewer and other experts. Results: The results will be included in the scoping review publication. Conclusions: This scoping review will identify key areas of ethical tensions and possible solutions and inform opportunities for empirical ethics studies.